Web-Based Sales System Development for Adi Jaya Electrical Store with Midtrans Payment Gateway Integration - Rina Noviana; Cesar Augusto Nino Putra; Devi Indriani; Dewi Andryani; Kartika Nor Ramadha; Rifki Amalia; Winarti Winarti (Jurnal Ilmiah Teknik, 2026)
MSMEs/UMKM remain a major driver of local economic activity, yet many still depend on offline, cash-based transactions that constrain operational efficiency. Digital sales platforms are therefore increasingly necessary to support faster, more reliable, and cashless purchasing processes. Objective: This study aims to develop and deploy a web-based sales system for Adi Jaya Electrical Store an MSME located at Ruko Taman Aster, Telaga Asih, Bekasi to improve transaction efficiency through online ordering and cashless payment. Methodology: The study adopts an applied information systems development approach using the Waterfall model. The system was implemented using PHP and a MySQL database, with requirements derived from field observation and interviews with the store owner. Functional verification was conducted using scenario-based black-box testing to assess whether key features operated according to the specified design. Findings: The website supports online product browsing and purchasing for electrical supplies (e.g., sockets, LED lamps, and cables) and integrates Midtrans as a payment gateway to facilitate non-cash transactions. Black-box testing indicates that the implemented functions and features operated as expected and were consistent with the design specifications. The system has been deployed and is accessible at https://adijaya.wuaze.com/. Implications: The platform provides a practical model for MSMEs to digitize sales operations, potentially improving transaction speed, reducing manual processing, and strengthening sales administration through structured order and payment management. Originality: This research delivers an operational MSME e-commerce implementation that combines end-to-end sales functionality with payment gateway integration and documented functional verification, extending prior work that often reports prototype development without demonstrable deployment readiness.